Isolation and characterization of bacteriophage against clinical isolates of AmpC beta lactamase–Producing Klebsiella pneumoniae from hospital wastewater - Manal Abdel Haleem A. Abusalah; Mai Abdel Haleem A. Abusalah; Chan Yean Yean; Ismail Aziah; Abdul Rahman Zaidah (PLoS ONE, 2025)
Background The increasing incidence of AmpC β-lactamase producing by K. pneumoniae has raised global alarm. Consequently, there is a crucial need for effective methods to inactivate pathogenic bacteria and mitigate the associated risks. Bacteriophage therapy has been demonstrated to be an effective and alternative approach for targeting and inactivating K. pneumoniae that produces AmpC. This study aimed to isolate and characterize the Klebsiella pneumoniae AmpC-specific phages from hospital wastewater. Methods The hospital wastewater samples were collected from the sewage water effluent of a tertiary hospital at Universiti Sains Malaysia, located on the east coast of Malaysia. These samples underwent serial filtration and centrifugation processes for phage recovery. The phage solutions were undergoing a screening test by spot assay using clinical isolates of Klebsiella pneumoniae AmpC strain as amplification hosts. The isolated AmpC-phages were further studied and characterised to determine the phage’s host range, temperature, pH, and chloroform stabilities. High-Resolution Transmission Electron Microscopy (HRTEM) was performed to determine the phage type. Results Thirty HWW samples were analyzed using four K. pneumoniae AmpC strains resulting in a total of 120 screening plates. The AmpC—Klebsiella pneumoniae (AmpC-KP) phages were detected in 31.70% (38/120) of the plates. The AmpC-KP phages had lytic diameters ranging from 1–3 mm, and a phage titer ranged from4×103–3.2×107 PFU/ml. The phages had a narrow–host range stable at a temperature range from -20–50˚C. The phages were also stable at pH ranging from 4 to 9 and at different concentrations of chloroform (5%,10%). Based on HRTEM, Siphoviridea was identified. Conclusions The AmpC-phages were abundant in hospital wastewater, and HWW was a good source for AmpC-KP phages. The isolated AmpC phages had a high effectivity and specificity for AmpC-KP with a narrow host range and could survive under harsh conditions such as (temperature, pH, and chloroform).